Comparative study of different arecanut-based cropping system models under sub Himalayan terai region - Sit, Arun Kumar; Shil, Sandip (Journal of Plantation Crops, 2025)
There is ample scope for intercropping in arecanut plantations for better utilisation of natural resources like land and sunlight. An experiment was conducted at CPCRI, Research Centre, Mohitnagar, with different crop combinations to establish a model for increased system productivity and better livelihood. Five arecanut-based cropping system models comprising different crop combinations were compared with the monocropping system of arecanut. The total system productivity ranged from 31.5 q/ha (control) to 131.1 q/ha across different models. Model II (arecanut + black pepper + acid lime + turmeric) emerged as the most productive, demonstrating superior total system productivity. This model resulted in notable increase in arecanut challi yield. Particularly noteworthy was the contribution of black pepper, which accounted for over 50% of the total system productivity. It is concluded that the arecanut-based cropping system is more advantageous than the monocropping of arecanut. Arecanut based cropping system has the potential to double the farmers’s income as the total system productivity has increased many folds over control. Among the different models studied, Model II with a crop combination of arecanut, black pepper, acid lime, and turmeric performed better withhigher returns. It is also suggested to the arecanut growers to adopt arecanut-based cropping system for their better livelihood.